Development of a model for estimating the sensitivity of Canadian peatlands to climate warning - Kettles, Inez; Tarnocai, Charles (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract Under current scenarios of increasing greenhouse gases, the expected increases in global temperatures have the potential to affect, in many areas, the peat- lands that now cover 14 % of the soil area of Canada. A model for estimating peatland sensitivity to climate warming was developed using published information on the current state of climate, vegetation, and permafrost together with the changes expected with a doubling of CO 2 . Calculations based on this sensitivity model and data for the areal extent and carbon content of organic soils in Canada, show that approximately 60 % of the area of Canadian peatlands is expected to be severely to extremely severely affected by climate warming. These peatlands, which are deemed most sensitive to climate warming, also contain 53 % of the 154 Gt of carbon found in organic soils.